Pembangunan Zona Integritas sebagai Upaya Peningkatan Kualitas Pelayanan Publik - Kusumawati, Bety Dwi; Askafi, Eka (Universitas Islam Kadiri, 2024)
The reform of the bureaucracy is an effort of absolute and fundamental reform for the system of governance related to various institutional, organizational, executive, and human resources aspects in order to establish a clean, accountable, and capable governance so that it can provide public services accurately, quickly, professionally, and, of course, clean from the practice of the CCN. As one of the steps to gain public confidence, the government has tried to implement the Integrity Zone as a step towards an area free from corruption. This qualitative research aims to examine the implementation of the Integration Zone in the Population and Civil Registration Service of the City of Blitar, the obstacles encountered in public service, aswell as possible efforts to improve the quality of public service. The findings show that the Integrity Zone has been implemented well since 2017 and provides increased access to key performance indicators, although some improvements in the service are required so that the agency can become the predecessor of a corruption-free territory that has never been achieved.